Coastal Resources Conservation in Indonesia: Issues, Policies, and Future Directions - Nikijuluw, Victor PH (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Blessed with vast coastal region, Indonesia has developed its economy by better utilizing the available resources therein. The coastal region, consisting of about 81,000 km shoreline and more than 17,000 small islands, has provided huge contribution to the national economy and served as the solid basis for various human activities. The region and its resources should be sustainably available and existed to support the country’s future economic development. Nevertheless there is a serious concern for its future, particularly regarding the status of the resources which essentially are the important life supporting system. The main coastal ecosystems that constitute Indonesian coastal region are mangrove forest, seagrass meadow, and coral reefs. Variety of goods and services are produced by these coastal ecosystems. Some of the goods and services are exploitable, usable, marketable, tradable, and highly priced. Some other goods and services, however, are remained unidentified, non-quantified, non-tradable, and unable to be monetized by using the existing technologies and market mechanisms. Consequently, the resources tend be underestimated and undervalued and eventually misused and mismanaged.